Enkele teologiese uitdagings rakende diakonia in van die Afrikaanse Suid-Afrikaanse kerke - Knoetze, Hannes (Verbum et ecclesia, 2023)
This article attends to the theological foundation of the diaconate from the missio trinitatis Dei and its implications, especially for the Afrikaans-speaking Reformed churches. The missio Dei , of the Father, Son, and Spirit is directed at the realities of this life. The new heaven and the new earth are not mutually exclusive. The earth is sanctified anew, man has created anew [recreated], and our bodies are raised anew [revived]. This new earth, a new man, and new life come through the merciful dikaiosune of the Father, the diakonia of the Son, and the koinonia of the Holy Spirit. The diaconate and the missionary ministry of the church are caught in the essence of God and therefore belong to the essence of missionary ecclesiology. From the trinitarian perspective, the purpose of the diaconate is described as well as the relationship between the diaconate, the church, and the kingdom. The last part of the article deals with salvation and diaconate and the implications of a trinitarian understanding of the diaconate for the understanding of salvation. Intradisciplinary and/or interdisciplinary implications: This article makes an interdisciplinary contribution to the theological discussion within the Afrikaans-speaking churches from the perspective of systematic and practical theology.